Body image dissatisfaction in pregnant and non-pregnant females is strongly predicted by immune activation and mucosa-derived activation of the tryptophan catabolite (TRYCAT) pathway. (3rd April 2018) - Roomruangwong, Chutima; Kanchanatawan, Buranee; Carvalho, André F.; Sirivichayakul, Sunee; Duleu, Sebastien; Geffard, Michel; Maes, Michael
Abstract: Objectives: The aim of the present study is to delineate the associations between body image dissatisfaction in pregnant women and immune-inflammatory biomarkers, i.e., C-reactive protein (CRP), zinc and IgA/IgM responses to tryptophan and tryptophan catabolites (TRYCATs). Methods: We assessed 49 pregnant and 24 non-pregnant females and assessed Body Image Satisfaction (BIS) scores at the end of term (T1), and 2–4 days (T2) and 4–6 weeks (T3) after delivery. Subjects were divided in those with a lowered BIS score (≤ 3) versus those with a higher score. Results: Logistic regression analysis showed that a lowered T1 BIS score was predicted by CRP levels and IgA responses to tryptophan (negative) and TRYCATs (positive), perinatal depression, body mass index (BMI) and age. The sum of quinolinic acid, kynurenine, 3-OH-kynurenine and 3-OH-anthranilic acid (reflecting brain quinolinic acid contents) was the single best predictor. In addition, a large part of the variance in the T1, T2 and T3 BIS scores was explained by IgA responses to tryptophan and TRYCATs, especially quinolinic acid. Conclusions: Body image dissatisfaction is strongly associated with inflammation and mucosa-derived IDO activation independently from depression, pregnancy, BMI and age. IgA responses to peripheral TRYCATs, which determine brain quinolinic acid concentrations, also predict body image dissatisfaction.